LEVELS OF FINANCIAL LITERACY IN TERMS OF THE ETHNICITY, GENDER, RELIGION AND LOCUS OF CONTROL OF COLLEGE STUDENTS - Romauli Nainggolan; Natalia Christiani; Novalita Fransisca Tungka (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2021)
During the pandemic, people must be adept in managing their private finances. Good money management skills are determined by the individual’s financial literacy. This research has five purposes. The first is to describe the level of financial literacy of college students. The second is to evaluate and analyze the different levels of financial literacy in terms of ethnicity. The third is to evaluate and analyze the different levels of financial literacy in terms of gender. The fourth is to evaluate and analyze the different levels of financial literacy in terms of religion. The fifth is to evaluate and analyze the different levels of financial literacy in terms of locus of control. This research samples 212 respondents majoring in English teacher training and education in four private universities. Because of this, this research evaluates the T value on the following variables: ethnicity, gender, religion, and locus of control. This research reveals a difference of financial literacy skills in terms of gender and locus of control. No different levels of financial literacy were found in terms of ethnicity and religion. In the future, there needs to be an improvement of financial literacy through formal and informal efforts. Keywords: ethnicity, Gender, religion, locus of control, financial literacy